NEW TECHNICAL MEANS FOR GETTING CONDITIONED OUTCROP AND THEIR RATIONAL USE (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
During the reconnaissance of column drilling, it has been observed that comparing the cost of one meter drilling run off, it is necessary to use different new technical means for additional outcrop. Using contemporary cataclastic reverse circulation machine-tools, we have concluded that it brings to high productivity in getting outcrop.
Keywords: econnaissance of column drilling; cataclastic reverse circulation machine-tools; core